The important lessons lurking in the history of meningococcal epidemiology - Ray Borrow; Jamie Findlow (Taylor & Francis Group, 2024)
ABSTRACTIntroduction The epidemiology of invasive meningococcal disease (IMD), a rare but potentially fatal illness, is typically described as unpredictable and subject to sporadic outbreaks.Areas covered Meningococcal epidemiology and vaccine use during the last ~ 200 years are examined within the context of meningococcal characterization and classification to guide future IMD prevention efforts.Expert opinion Historical and contemporary data highlight the dynamic nature of meningococcal epidemiology, with continued emergence of hyperinvasive clones and affected regions. Recent shifts include global increases in serogroup W disease, meningococcal antimicrobial resistance (AMR), and meningococcal urethritis; additionally, unvaccinated populations have experienced disease resurgences following lifting of COVID-19 restrictions. Despite these changes, a close analysis of meningococcal epidemiology indicates consistent dominance of serogroups A, B, C, W, and Y and elevated IMD rates among infants and young children, adolescents/young adults, and older adults. Demonstrably effective vaccines against all 5 major disease-causing serogroups are available, and their prophylactic use represents a powerful weapon against IMD, including AMR. The World Health Organization's goal of defeating meningitis by the year 2030 demands broad protection against IMD, which in turn indicates an urgent need to expand meningococcal vaccination programs across major disease-causing serogroups and age-related risk groups.